Application of DEA method in measuring of market efficiency of banks in Bosnia and Herzegovina and reflection of the COVID-19 - Beriz Čivić (International Econometric Review (IER), 2022)
By using the DEA method, the paper measures market efficiency of the banks in Bosnia and Herzegovina in the period 2017-2020, in the context of challenges caused by the COVID-19. The aims of the research are: a) to measure market efficiency of the banks in Bosnia and Herzegovina and rank them using the DEA method (applying three models CCR-O, BCC-O, and Window-I-C), b) establish the effect of the COVID-19 pandemic on market efficiency of the observed banks, and c) established the link between the volume of digital banking services usage and market efficiency of the observed banks. The research results show that in 2020, when the COVID-19 appeared, CCR-O and BCC-O models revealed a decrease in market efficiency for 73.9% of the observed banks while Window-I-C model revealed lower market efficiency for all the observed banks. The regression analysis applied showed a significant link between the volume of digital banking services usage market efficiency of the observed banks. The regression model was established, pointing to a significant importance of independent variables for the prediction of the dependent variable.
Keywords: M31; 330; Market efficiency; Banks; DEA method